2016
DOI: 10.1007/s11259-016-9664-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HIF-1α ODD domain fused canine caspase 3 by EGFR promoter-driven adenovirus vector induces cytotoxicity in canine breast tumor cells under hypoxia

Abstract: Adenovirus (Ad) vectors are widely used in cancer gene therapies. However, compared to human patients, relatively limited information is available on gene transduction efficiency or cell-specific cytotoxicity in canine tumor cells transduced with Ad vectors. Since epidermal growth factor receptor (EGFR) is highly expressed on canine breast tumor cells, we sought to develop an Ad vector based on the RGD fiber-mutant adenovirus vector (AdRGD) that expresses canine caspase 3 under the control of EGFR promoter. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…As ODD-based reporters rely on naturally present cellular enzymes for their functioning, phylogenetic relationships should be considered. Thus, Okamoto et al, in the course of directed gene therapy for canine breast tumors development successfully implemented reporters based on human ODD because its amino acid sequence is identical to canine ODD [97]. In another study, it was shown that the ability of PHD from Drosophila to recognize proline-containing peptides derived from human HIF-isoforms was reduced by 20-50% when compared to those from Sima (Drosophila homolog of HIF-1α) [98].…”
Section: Odd-based Degradation Reportersmentioning
confidence: 99%
See 1 more Smart Citation
“…As ODD-based reporters rely on naturally present cellular enzymes for their functioning, phylogenetic relationships should be considered. Thus, Okamoto et al, in the course of directed gene therapy for canine breast tumors development successfully implemented reporters based on human ODD because its amino acid sequence is identical to canine ODD [97]. In another study, it was shown that the ability of PHD from Drosophila to recognize proline-containing peptides derived from human HIF-isoforms was reduced by 20-50% when compared to those from Sima (Drosophila homolog of HIF-1α) [98].…”
Section: Odd-based Degradation Reportersmentioning
confidence: 99%
“…ODD-based reporters have significantly contributed to our understanding of HIF signaling and facilitated the development of targeted gene therapy [97]. They have allowed for the creation of efficient PHDs inhibitors screening systems in cellular models that are free from the artifacts characteristic of in vitro assays attributed to the low activity of the purified PHDs, possible iron-overload during such protocols, and the insufficient affinity of substrate peptides compared to HIFα subunits [93].…”
Section: Odd-based Degradation Reportersmentioning
confidence: 99%
“…Cell culture HEK293 (human embryonic kidney) cells were obtained from the Human Science Research Resources Bank (Ibaraki, Japan) and cultured as reported previously [38]. The Lenti-X 293 T cell line was purchased from Takara.…”
Section: Rt-qpcrmentioning
confidence: 99%
“…Choosing the optimal promoter, i.e., a tumor-specific promoter, is a key factor for achieving successful tumor-specific transgene expression. In a previous study, we evaluated tumor cell-specific transgene expression by a human EGFR ( hEGFR ) promoter-driven adenovirus vector in a canine mammary tumor cell line and showed the potential viability of using the hEGFR promoter for gene therapy in canine mammary tumors [15]. However, little is known about whether the EGFR promoter can induce efficient, tumor cell-specific transgene expression in CUC cells, even when EGFR is overexpressed in these tumors.…”
mentioning
confidence: 99%
“…The hEGFR promoter-containing plasmid pHMhEGFR was constructed as described previously [15]. The hTERT promoter, located immediately upstream from the ATG translation initiation site (positions −458 to −2, corresponding to positions −378 to +78 from the transcription start site) [16], was cloned from human genomic DNA by polymerase chain reaction (PCR) using PrimeSTAR Max DNA Polymerase (Takara Bio, Kusatsu, Japan) and the following primers: forward primer, 5′-CGGAATTCATCATGGCCCCTCCCTCG-3′ and reverse primer, 5′-GCTCTAGACGCGGGGGTGGCCGG-3′.…”
mentioning
confidence: 99%